2017
DOI: 10.1007/s00425-017-2718-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling of red and blue potatoes revealed cultivar and tissue specific patterns for anthocyanins and other polyphenols

Abstract: Metabolite profiling of tuber flesh and peel for selected colored potato varieties revealed cultivar and tissue specific profiles of anthocyanins and other polyphenols with variations in composition and concentration. Starchy tubers of Solanum tuberosum are a staple crop and food in many countries. Among cultivated potato varieties a huge biodiversity exists, including an increasing number of red and purple colored cultivars. This coloration relates to the accumulation of anthocyanins and is supposed to offer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 56 publications
6
67
0
1
Order By: Relevance
“…After centrifugation, 5 µL of the supernatant were injected per sample. Anthocyanins were analysed by LC-UV/MS as described in Oertel et al (2017) . Details for LC-UV/MS and MS/MS fragmentation analyses are provided in Supplementary Methods .…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation, 5 µL of the supernatant were injected per sample. Anthocyanins were analysed by LC-UV/MS as described in Oertel et al (2017) . Details for LC-UV/MS and MS/MS fragmentation analyses are provided in Supplementary Methods .…”
Section: Methodsmentioning
confidence: 99%
“…The potato ( Solanum tuberosum L.) is a major staple food for humans and the fourth largest crop grown worldwide, after rice, wheat and maize . A large biodiversity exists among potato cultivars, including an increasing number of red and purple coloured varieties . These potatoes have been receiving increased interest from researchers, industry and consumers due to their higher nutritional value and more attractive colour than traditional, light‐fleshed tubers.…”
Section: Introductionmentioning
confidence: 99%
“…1 A large biodiversity exists among potato cultivars, including an increasing number of red and purple coloured varieties. 2,3 These potatoes have been receiving increased interest from researchers, industry and consumers due to their higher nutritional value and more attractive colour than traditional, light-fleshed tubers. In general, due to higher levels of antioxidants, such as phenolic compounds, red-and purple-fleshed cultivars may be healthier compared with white cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Acylated forms of anthocyanins were reported to be the main compounds responsible for the red and purple flesh color of potatoes [94]. In particular, the deep-purple color of potato flesh and skin is associated with the presence of petunidin derivatives, although studies on metabolite profiling revealed a genotype-and tissue-specific pattern regarding the anthocyanin composition [22]. Petunidin was the major anthocyanidin compound found both in the flesh and the peel of purple potato varieties studied by Yine et al [21].…”
Section: Potatomentioning
confidence: 99%